Sosialisasi Upaya Pencegahan Covid 19 di Area Mesjid Shirotol Mustaqim Kelurahan Batunadua Jae, Kecamatan Padangsidimpuan Batunadua Kota Padangsidimpuan - Simamora, Febrina Angraini; Daulay, Nanda Masraini (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Covid-19 is a disease caused by a new type of corona virus that appeared at the end of 2019 for the first time in Wuhan, China which is currently causing a pandemic in almost all over the world. In an effort to prevent the increasingly widespread transmission of Covid-19. The government urges all levels of society to take various preventive measures such as carrying out physical distancing, using masks, washing hands regularly, increasing endurance and maintaining health. The socialization activity for the prevention of Covid 19 in the mosque area aims to increase knowledge and change the behavior of the community, especially the Shirotol Mustaqim congregation, so that they can continue to make efforts to prevent the spread of Covid 19 during the 5 daily prayers as well as tarawih and tadarusan prayers which are held at the mosque during this month of Ramadan . This activity consisted of some counseling and leaflet distribution at the nazir of the mosque and the shirotol mustaqim mosque congregation. The results of the evaluation during the activity process were obtained that as many as 90% (19 participants) experienced increased knowledge regarding efforts to prevent Covid 19. With this socialization, it is hoped that it will be able to increase the knowledge and behavior of the community to always make efforts to prevent Covid 19 in any activity.